2021
DOI: 10.1080/19942060.2021.1922124
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of COVID-19 virus by cough-induced particles in an airliner cabin section

Abstract: With airborne transmissions found as one of the major transmission routes of SARS-CoV-2, its transmission in airliner cabin environments drew special attention due to high number of imported cases and in-cabin transmissions. This study numerically investigated the transmission of COVID-19 by cough-induced particles in a cabin section of Boeing 737 model. One passenger was coughing in each case, while cough particles with measured size distributions were released during coughs and were tracked using the Lagrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Many experimental and computational fluid dynamics (CFD) papers 9–32 can be found in the literature in which the MV flow in different airplane cabin configurations (e.g., single‐aisle as the B737‐200, A320, and MD‐82, or twin‐aisle as the B767‐300 or A380) was investigated and characterized in terms of its mean and instantaneous flow patterns, distributions of velocity, turbulence, temperature, relative humidity, pressure, and vorticity. The ventilation performance regarding the distribution of (gaseous) contaminants, 11,13,15,17,28,29,32,33–37 droplet and aerosol deposition/dispersion, 15,32,38–45 age of air, 13,27,46,47 thermal comfort (predicted mean vote, predicted percentage dissatisfied) 47–49 and heat 27,48,50 or contaminant 13,35 removal was also reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many experimental and computational fluid dynamics (CFD) papers 9–32 can be found in the literature in which the MV flow in different airplane cabin configurations (e.g., single‐aisle as the B737‐200, A320, and MD‐82, or twin‐aisle as the B767‐300 or A380) was investigated and characterized in terms of its mean and instantaneous flow patterns, distributions of velocity, turbulence, temperature, relative humidity, pressure, and vorticity. The ventilation performance regarding the distribution of (gaseous) contaminants, 11,13,15,17,28,29,32,33–37 droplet and aerosol deposition/dispersion, 15,32,38–45 age of air, 13,27,46,47 thermal comfort (predicted mean vote, predicted percentage dissatisfied) 47–49 and heat 27,48,50 or contaminant 13,35 removal was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…The ventilation performance regarding the distribution of (gaseous) contaminants, 11,13,15,17,28,29,32,[33][34][35][36][37] droplet and aerosol deposition/ dispersion, 15,32,[38][39][40][41][42][43][44][45] age of air, 13,27,46,47 thermal comfort (predicted mean vote, predicted percentage dissatisfied) [47][48][49] and heat 27,48,50 or contaminant 13,35 removal was also reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are more than two billion people traveling by air every year [2]. The microenvironment in the commercial aircraft cabin is enclosed, which provides a good place for the virus to spread among passengers [3,4]. Long-distance air travel makes the virus spread broadly and rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…The other is to treat solid particles or droplets as a discrete phase material and use the Lagrangian's method to calculate the motion characteristics of each particle [14][15][16]. Some in-cabin studies use the discretization method to obtain the trajectory of virus particles [4,17,18]. In addition, Sandro et al replaced respiratory pathogens with smoke particles and concluded that 60% of the particles sink to the surfaces of the cabin due to gravity during the propagation process [19].…”
Section: Introductionmentioning
confidence: 99%